The Influence of Profitability and Capital Structure on Firm Value with Environmental, Social, and Governance (ESG) as a Moderating Variable in Banking Companies on the Indonesia Stock Exchange (2019-2023) - Pristisani Purba; F. Defung; Musdalifah Azis (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the influence of profitability and capital structure on firm value with Environmental, Social, and Governance (ESG) as a moderating variable in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The research method uses panel data regression analysis with a Moderated Regression Analysis (MRA) approach. The research sample consists of 6 banks selected through purposive sampling technique. The results show that: (1) Profitability (ROA) does not have a significant effect on firm value; (2) Capital structure (DER) has a significant positive effect on firm value; (3) ESG strengthens the relationship between capital structure and firm value; (4) ESG does not significantly moderate the relationship between profitability and firm value. The Adjusted R² value of 0.4754 indicates that the model is fairly representative in explaining the variation in firm value. The implications of this research emphasize the importance of integrating ESG into banking financial strategies to enhance long-term firm value.